A convergence computational scheme for system of integral equation using finite element method. (5th February 2020) - Zeidabadi, Hamed; Heidari, Mohammad
In this paper, a computational scheme for extracting approximate solutions of system of integral equations is proposed. For this purpose, by considering the variational form of the problem and using finite element method, the system of integral equations are reduced to a system of algebraic equations, that are solved by an efficient algorithm. Also, the existence and uniqueness of the system of integral equations are illustrated and the convergence of the approximate solution to the exact solution is investigated. Finally, the effectiveness of the proposed method is discussed by comparing with the results of the given approaches in Babolian and Mordad (2011) and Jafarian et al. (2013).